Die herfsfees en die koningsrite by Bet-El as interteks van Amos 7: 1 0-8: 14 en Hosea 9: 1-9 - Breytenbach, Andries (Hervormde teologiese studies, 1997)
The autumnal festival and the royal rite at Bethel as an intertext of Amos 7:10-8:14 and Hosea 9:1-9. It is argued that a text from the Samaritan Liturgy which describes a royal rite at Bethel on the last day of the autumnal festival, represents a reliable tradition. This text, as well as Deuteronomy 26:2-15 to which it is closely related, is used as the basis for a reconstruction of a royal rite at Bethel during the time of the monarchy. Amos 7:10-8:14 and Hosea 9:1-9 are read against this background. The said prophecies state exactly the opposite of what was expressed and intended by the royal rite. This accounts for the vehement reaction against Amos and Hosea from the side of the priests.